The APTT Response of Pregnant Plasma to Unfractionated Heparin - Chunilal, S.D.; Young, E.; Johnston, M.A.; Robertson, C.; Naguit, I.; Stevens, P.; Galashan, D.; Oskamp, M.L.; Brennan, B.; Ginsberg, J.S. (Thrombosis and Haemostasis, 2002)
Pregnancy is associated with a physiological increase in coagulation factors and heparin binding proteins; both can affect the activated partial thromboplastin time (APTT) in response to unfractionated heparin (UFH) invalidating the use of a non-pregnant APTT therapeutic range. We compared the anticoagulant response of UFH added in vitro to the plasma of 13 pregnant (third trimester) and 15 nonpregnant women to determine whether the measured APTT and antifactor Xa activities are lower in pregnancy. Increasing concentrations of UFH were added to platelet-poor plasma from each subject and the APTT and anti-factor Xa activity were measured. The amount of UFH which was reversibly bound and neutralised by plasma heparin binding proteins was assessed by comparing the anti-factor Xa activity before and after addition of low affinity heparin (LAH). Fibrinogen, von Willebrand factor antigen (vWF Ag) and factor VIII levels, were also measured. The APTT response, assessed by the slope of the regression line of log APTT versus added heparin concentration, was attenuated in pregnant plasma (0.76 s/U/mL versus 1.2 s/U/mL, p = 0.005) and was highly correlated to increased non-specific plasma protein binding (47% versus 35% p <0.01) and increased fibrinogen (5.1g/L versus 2.8 g/L, p <0.01) and factor VIII activity (2.7 U/mL versus 1.2 U/mL, p <0.01). Thus, to achieve the same heparin level, pregnant women require higher daily doses of UFH than non-pregnant women. However, if UFH dose adjustments during the third trimester are based upon a non-pregnant APTT therapeutic range, systematic overdosing of pregnant women will result, possibly increasing the risk of bleeding and osteoporosis.
Keywords: Unfractionated heparin; pregnancy; activated partial thromboplastin time (APTT); anti-factor Xa activity